Intellectual Leadership Research: A Bibliometric Review with VOSviewer - Özyurt, Rana; ÜLER, Elif; AKDEMİR, Ali (International Journal of Contemporary Economics and Administrative Sciences, 2026)
Purpose: The aim of this study is to systematically examine the concept of intellectual leadership, which is an emerging leadership approach, and to evaluate scientific publications regarding the concept using the bibliometric analysis method. As a result of the analyses carried out through the VOSviewer program, several literature gaps regarding the concept were identified, and it was aimed to guide future studies. Method: The concept of “Intellectual Leadership” was scanned as a keyword in the Web of Science (WoS) database as of February 2025, using the “all fields” search criterion. A total of 198 publications were accessed and analyzed through VOSviewer software after data cleaning. In the analysis, network maps of the concept were revealed based on co-authorship, citation, country, institution, bibliometric author matching, and bibliometric publication matching. In addition, collaborations, trends, and thematic concentrations regarding the concept were examined. Findings: It was observed that the concept was studied mainly between 2012 and 2022, while collaborations regarding this relatively new concept remained limited. Citation and co-authorship analyses revealed the existence of clusters centered around certain institutions and authors. Country- and institution-based analyses indicate that the concept has an increasing visibility in the international literature. Limitations: The study is limited to publications indexed in the WoS database. The exclusion of other important databases, such as Scopus, constitutes one of the main limitations of the study. Originality Value: Since the concept of intellectual leadership is a rising field in the literature, this study reveals existing gaps and contributes to making the concept more visible. In addition, it offers suggestions for future research in both methodological and thematic terms.